2022
DOI: 10.1136/jnis-2022-019557
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy in minor stroke due to isolated M2 occlusion: a multicenter retrospective matched analysis

Abstract: BackgroundThe purpose of this study was to evaluate the effectiveness of mechanical thrombectomy (MT) in patients with isolated M2 occlusion and minor symptoms and identify possible baseline predictors of clinical outcome.MethodsThe databases of 16 high-volume stroke centers were retrospectively screened for consecutive patients with isolated M2 occlusion and a baseline National Institutes of Health Stroke Scale (NIHSS) score ≤5 who received either early MT (eMT) or best medical management (BMM) with the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Although with some limits due to the ischemic side, higher NIHSS reflects larger ischemic tissue volume ( 8 ). Given that CC status has been previously associated with the extent of ischemic core ( 3 ), NIHSS may represent a surrogate of it ( 24 ). The association of NIHSS with CC seems consistent across studies, and we found a similar magnitude of the effect of NIHSS on collateral status compared with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although with some limits due to the ischemic side, higher NIHSS reflects larger ischemic tissue volume ( 8 ). Given that CC status has been previously associated with the extent of ischemic core ( 3 ), NIHSS may represent a surrogate of it ( 24 ). The association of NIHSS with CC seems consistent across studies, and we found a similar magnitude of the effect of NIHSS on collateral status compared with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…After full-text reading, 20 articles were excluded for the following reasons: (1) the medical treatment group was not relevant, (2) the mild stroke was not relevant, (3) patients with posterior circulation occlusion were included, and (4) the outcomes of the EVT and medical treatment groups were missing. Finally, 14 articles12 18–20 27–36 were found to be eligible, with 1819 and 2516 patients treated with EVT and medical treatment, respectively (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the details of the design and baseline characteristics of each included study. Furthermore, PS-based methods adjusted analysis was reported in 10 studies,18–20 28 29 31–35 whose main characteristics are summarized in online supplemental table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexandre et al showed in their study that early MT is likely superior to BMT in patients with LVO, even if their NIHSS on admission is low (≤ 5) 24 . However, this is not necessarily the same for DMVO, as another study showed no benefit of early MT compared with BMT in patients with NIHSS ≤ 5 and isolated M2 occlusions 25 . In our study, subgroup analysis could not be performed to address this issue because of the limited number of patients.…”
Section: Discussionmentioning
confidence: 95%